Analisis Determinan Kepatuhan Penggunaan Alat Pelindung Diri Terhadap Covid-19 Pada Pegawai KKP Kelas II Samarinda - Maulana, Ardya Nisfu; Adit, Nino; Tonapa, Emilia; Hazanah, Sri (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2024)
Background: The Covid-19 pandemic has emerged as a global health crisis, affecting various sectors including those serving in the Port Health Office (PHO), who are particularly vulnerable to the risks posed by the pandemic. Amidst this situation, 19 positive Covid-19 cases have been identified among the employees of KKP Class II Samarinda. The utilization of Personal Protective Equipment (PPE) stands as a crucial preventive measure against the transmission of Covid-19, especially within the workforce. This research aims to elucidate the profile of determinants influencing the compliance in using PPE concerning Covid-19 among the personnel of the Port Health Office Class II Samarinda, in the year 2023.Method: This type of research was analytic observational with a cross-sectional design. The study sample amounted to 62 employees who were determined using the total sampling technique. Data collection methods through filling out questionnaire sheets. Data analysis using Chi-Square test, Fisher test and Gamma test.Research Results: The results showed that there were three variables associated with compliance with the use of Personal Protective Equipment in COVID-19 prevention. The three variables include level of education, length of work, and level of knowledge. Uncorrelated variables are age and sex. The research land is expected to establish policies in the form of reward and punishment related to efforts to increase compliance with the use of Personal Protective Equipment.Conclusions: There is a correlation between length of employment, level of education, and knowledge with compliance in using Personal Protective Equipment (PPE).Keywords: Compliance, Personal Protective Equipment, COVID-19